The role of sound reasoning in hadith-text examination - Khan, Israr Ahmad (London Academy of Iranian Studies, 2010)
There is no denying the fact that the compendia of Prophetic traditions (Hadith) comprise all categories of reports: highly authentic, authentic, deemed to be authentic, weak, and fabricated. Muslim scholars developed several criteria to authenticate hadith. But these criteria are generally to authenticate the chain of narrators through which hadith is reported and recorded. Hadith experts concluded that the authentication of the Chain ensures authenticity of the Text reported. That is why, almost all hadith authorities concentrate on the authentication of hadith by authenticating the Chain in the hadithreport. Very few scholars have paid attention to verify the Text of hadith independently. It is not always necessary that if the Chain seems to be authentic, the Text will also be authentic. In order to check the position of the Text of hadith there should certainly be some logically acceptable criteria. One such criterion to check the reliability of hadith- Text is human reason. The Qur’an has, a number of times, invited man to use his reason in determining the nature of the things he tackles or deals with. It is, then, quite logical to read, treat and deal with rationally what has been recorded by Muslim scholars as sayings and doings of Prophet Muhammad (s.a.w.). This paper represents a humble attempt to apply the criterion “sound reasoning” to some selected hadith as recorded in al-Bukhari’s work, Al-Jami‘ al-Sahih and Muslim’s compilation of hadith, Al-Sahih. The selected traditions are twelve (12). An effort has been made to make a critical analysis of the reported version of hadith. The objective of this exercise is not to discredit the value of hadith in Islamic life. But the task carried out in the paper is to ascertain whether there are lacunae in the reported wordings attributed to the Prophet Muhammad (s.a.w.).